Assessing the Role of Legislation in the Development of Nigerian Solid Mineral Sector - , O. D. Eniowo; , Z. O. Opafunso; , A. O. Owolabi (Archives of Current Research International, 2017)
This study assesses the role of legislation in the development of the Nigerian solid mineral sector. The aim of the assessment is to determine how well Nigeria mining companies comply with some key provisions of mining and mineral legislation and also to determine the influence of these legislations on the mining industries. For the purpose of this study, the Mining Act of 2007; The Mining Regulations of 2011; The explosives Act of 1964 and Explosives Regulations of 1967 which are the major legislations governing the activities of mining in Nigeria were reviewed, some specific provisions were extracted and compliance to theses extracted provisions were assessed. Thirty mining firms were assessed with the aid of a questionnaire in order to determine the level of their compliance to the identified provisions of mining legislations. Data acquired and assessed include compliance of these mineral industries with the provisions of the mining legislations on explosives magazines administration; Safety and health requirements; Production reporting and royalty payments. The results indicate that the mining industries assessed comply with most of the requirements on safety and health and also with royalty payments. It is however revealed that most of the provisions of mining legislations on explosives magazine administration are not well complied with.